Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Certainly! Let's solve the given problem step-by-step.
Given matrices:
[tex]\[ A = \begin{bmatrix} 3 & 4 \\ -5 & -1 \end{bmatrix} \][/tex]
[tex]\[ 3A + B = \begin{bmatrix} 2 & 8 \\ 3 & -4 \end{bmatrix} \][/tex]
### i) Finding Matrix [tex]\(B\)[/tex]
First, isolate [tex]\(B\)[/tex] from the equation [tex]\(3A + B = \text{some matrix}\)[/tex]:
[tex]\[ B = \begin{bmatrix} 2 & 8 \\ 3 & -4 \end{bmatrix} - 3A \][/tex]
Next, calculate [tex]\(3A\)[/tex]:
[tex]\[ 3A = 3 \times \begin{bmatrix} 3 & 4 \\ -5 & -1 \end{bmatrix} = \begin{bmatrix} 3 \cdot 3 & 3 \cdot 4 \\ 3 \cdot (-5) & 3 \cdot (-1) \end{bmatrix} = \begin{bmatrix} 9 & 12 \\ -15 & -3 \end{bmatrix} \][/tex]
Subtract [tex]\(3A\)[/tex] from the given matrix:
[tex]\[ B = \begin{bmatrix} 2 & 8 \\ 3 & -4 \end{bmatrix} - \begin{bmatrix} 9 & 12 \\ -15 & -3 \end{bmatrix} = \begin{bmatrix} 2 - 9 & 8 - 12 \\ 3 - (-15) & -4 - (-3) \end{bmatrix} = \begin{bmatrix} -7 & -4 \\ 18 & -1 \end{bmatrix} \][/tex]
Thus, matrix [tex]\(B\)[/tex] is:
[tex]\[ B = \begin{bmatrix} -7 & -4 \\ 18 & -1 \end{bmatrix} \][/tex]
### ii) Finding [tex]\(AB\)[/tex]
Now, we need to find the product [tex]\(AB\)[/tex]:
[tex]\[ A = \begin{bmatrix} 3 & 4 \\ -5 & -1 \end{bmatrix} \][/tex]
[tex]\[ B = \begin{bmatrix} -7 & -4 \\ 18 & -1 \end{bmatrix} \][/tex]
To multiply two matrices, we follow the rule where each element of the resulting matrix is the dot product of corresponding rows and columns.
So,
[tex]\[ AB = \begin{bmatrix} 3 & 4 \\ -5 & -1 \end{bmatrix} \times \begin{bmatrix} -7 & -4 \\ 18 & -1 \end{bmatrix} \][/tex]
Calculate each element of the resulting matrix:
1. First row, first column:
[tex]\[ (3 \times -7) + (4 \times 18) = -21 + 72 = 51 \][/tex]
2. First row, second column:
[tex]\[ (3 \times -4) + (4 \times -1) = -12 - 4 = -16 \][/tex]
3. Second row, first column:
[tex]\[ (-5 \times -7) + (-1 \times 18) = 35 - 18 = 17 \][/tex]
4. Second row, second column:
[tex]\[ (-5 \times -4) + (-1 \times -1) = 20 + 1 = 21 \][/tex]
Thus, the resulting matrix [tex]\(AB\)[/tex] is:
[tex]\[ AB = \begin{bmatrix} 51 & -16 \\ 17 & 21 \end{bmatrix} \][/tex]
### Summary
1. Matrix [tex]\(B\)[/tex] is:
[tex]\[ B = \begin{bmatrix} -7 & -4 \\ 18 & -1 \end{bmatrix} \][/tex]
2. The product [tex]\(AB\)[/tex] is:
[tex]\[ AB = \begin{bmatrix} 51 & -16 \\ 17 & 21 \end{bmatrix} \][/tex]
Given matrices:
[tex]\[ A = \begin{bmatrix} 3 & 4 \\ -5 & -1 \end{bmatrix} \][/tex]
[tex]\[ 3A + B = \begin{bmatrix} 2 & 8 \\ 3 & -4 \end{bmatrix} \][/tex]
### i) Finding Matrix [tex]\(B\)[/tex]
First, isolate [tex]\(B\)[/tex] from the equation [tex]\(3A + B = \text{some matrix}\)[/tex]:
[tex]\[ B = \begin{bmatrix} 2 & 8 \\ 3 & -4 \end{bmatrix} - 3A \][/tex]
Next, calculate [tex]\(3A\)[/tex]:
[tex]\[ 3A = 3 \times \begin{bmatrix} 3 & 4 \\ -5 & -1 \end{bmatrix} = \begin{bmatrix} 3 \cdot 3 & 3 \cdot 4 \\ 3 \cdot (-5) & 3 \cdot (-1) \end{bmatrix} = \begin{bmatrix} 9 & 12 \\ -15 & -3 \end{bmatrix} \][/tex]
Subtract [tex]\(3A\)[/tex] from the given matrix:
[tex]\[ B = \begin{bmatrix} 2 & 8 \\ 3 & -4 \end{bmatrix} - \begin{bmatrix} 9 & 12 \\ -15 & -3 \end{bmatrix} = \begin{bmatrix} 2 - 9 & 8 - 12 \\ 3 - (-15) & -4 - (-3) \end{bmatrix} = \begin{bmatrix} -7 & -4 \\ 18 & -1 \end{bmatrix} \][/tex]
Thus, matrix [tex]\(B\)[/tex] is:
[tex]\[ B = \begin{bmatrix} -7 & -4 \\ 18 & -1 \end{bmatrix} \][/tex]
### ii) Finding [tex]\(AB\)[/tex]
Now, we need to find the product [tex]\(AB\)[/tex]:
[tex]\[ A = \begin{bmatrix} 3 & 4 \\ -5 & -1 \end{bmatrix} \][/tex]
[tex]\[ B = \begin{bmatrix} -7 & -4 \\ 18 & -1 \end{bmatrix} \][/tex]
To multiply two matrices, we follow the rule where each element of the resulting matrix is the dot product of corresponding rows and columns.
So,
[tex]\[ AB = \begin{bmatrix} 3 & 4 \\ -5 & -1 \end{bmatrix} \times \begin{bmatrix} -7 & -4 \\ 18 & -1 \end{bmatrix} \][/tex]
Calculate each element of the resulting matrix:
1. First row, first column:
[tex]\[ (3 \times -7) + (4 \times 18) = -21 + 72 = 51 \][/tex]
2. First row, second column:
[tex]\[ (3 \times -4) + (4 \times -1) = -12 - 4 = -16 \][/tex]
3. Second row, first column:
[tex]\[ (-5 \times -7) + (-1 \times 18) = 35 - 18 = 17 \][/tex]
4. Second row, second column:
[tex]\[ (-5 \times -4) + (-1 \times -1) = 20 + 1 = 21 \][/tex]
Thus, the resulting matrix [tex]\(AB\)[/tex] is:
[tex]\[ AB = \begin{bmatrix} 51 & -16 \\ 17 & 21 \end{bmatrix} \][/tex]
### Summary
1. Matrix [tex]\(B\)[/tex] is:
[tex]\[ B = \begin{bmatrix} -7 & -4 \\ 18 & -1 \end{bmatrix} \][/tex]
2. The product [tex]\(AB\)[/tex] is:
[tex]\[ AB = \begin{bmatrix} 51 & -16 \\ 17 & 21 \end{bmatrix} \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.